The Impact of Endometriosis on Women’s Quality of Life and Sexual Life - Melike DİŞSİZ; Beyzanur İŞBAY; Sevilay AYDIN; Dilek BİNGÖL; Özlem ÖNER; Resul KARAKUŞ (Archives of Health Science and Research)
Objective: This study was carried out to determine the effect of endometriosis on women’s sexual life and quality of life.